Improving outcomes for patients with medication‐resistant anxiety: effects of collaborative care with cognitive behavioral therapy. Issue 12 (24th October 2016) - Campbell‐Sills, Laura; Roy‐Byrne, Peter P.; Craske, Michelle G.; Bystritsky, Alexander; Sullivan, Greer; Stein, Murray B.
Abstract : Background: Many patients with anxiety disorders remain symptomatic after receiving evidence‐based treatment, yet research on treatment‐resistant anxiety is limited. We evaluated effects of cognitive behavioral therapy (CBT) on outcomes of patients with medication‐resistant anxiety disorders using data from the Coordinated Anxiety Learning and Management (CALM) trial. Methods: Primary care patients who met study entry criteria (including DSM‐IV diagnosis of generalized anxiety disorder, panic disorder, posttraumatic stress disorder, or social anxiety disorder) despite ongoing pharmacotherapy of appropriate type, dose, and duration were classified as medication resistant ( n = 227). Logistic regression was used to estimate effects of CALM's CBT program (CALM‐CBT; chosen by 104 of 117 medication‐resistant patients randomized to CALM) versus usual care (UC; n = 110) on response [≥ 50% reduction of 12‐item Brief Symptom Inventory (BSI‐12) anxiety and somatic symptom score] and remission (BSI‐12 < 6) at 6, 12, and 18 months. Within‐group analyses examined outcomes by treatment choice (CBT vs. CBT plus medication management) and CBT dose. Results: Approximately 58% of medication‐resistant CALM‐CBT patients responded and 46% remitted during the study. Relative to UC, CALM‐CBT was associated with greater response at 6 months (AOR = 3.78, 95% CI 2.02‐7.07) and 12 months (AOR = 2.49, 95% CI 1.36‐4.58) and remission at 6, 12, and 18 months (AORs = 2.44 to 3.18). Patients in CBT plus medication management fared no better than those in CBT only. Some evidence suggested higher CBT dose produced better outcomes. Conclusions: CBT can improve outcomes for patients whose anxiety symptoms are resistant to standard pharmacotherapy.